2020
DOI: 10.3892/ol.2020.11469
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of keratin 17 by lentivirus‑mediated short hairpin RNA inhibits the proliferation of PANC‑1 human pancreatic cancer cells

Abstract: , KRT17 knockdown inhibited in vivo tumor growth. KRT17 knockdown induced dysregulation of ERK1/2 and upregulation of the pro-apoptotic Bcl-2 protein Bad. In conclusion, the present study demonstrated that elevated KRT17 levels are positively associated with pancreatic cancer progression; KRT17 knockdown suppressed cell growth, colony formation, migration and tumor growth, and induced apoptosis and cell cycle arrest, affecting ERK1/2/Bad signaling. Therefore, the results of the present study suggested that KRT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 47 publications
0
14
1
Order By: Relevance
“…Intriguingly, when we analyzed the downstream pathways of KRT17, we noticed that the ablation of KRT17 also leads to the deactivation of both AKT and ERK pathway. It was reported that KRT17 deficiency impairs the activation of ERK, while makes little difference on AKT activation in pancreatic cancer cells [21], which disagrees with our present results. However, a recent in vitro and in vivo study on osteosarcoma cells have shown that KRT17 participates in the regulation of the AKT/mTOR/HIFα pathway [32].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Intriguingly, when we analyzed the downstream pathways of KRT17, we noticed that the ablation of KRT17 also leads to the deactivation of both AKT and ERK pathway. It was reported that KRT17 deficiency impairs the activation of ERK, while makes little difference on AKT activation in pancreatic cancer cells [21], which disagrees with our present results. However, a recent in vitro and in vivo study on osteosarcoma cells have shown that KRT17 participates in the regulation of the AKT/mTOR/HIFα pathway [32].…”
Section: Discussioncontrasting
confidence: 99%
“…For instance, KRT17 ablation suppresses the proliferation of oral squamous cell carcinoma in vitro and in vivo in nude mice [24]. Similarly, the pro-proliferation function of KRT17 was also observed in pancreatic cancer cell line [21]. It was demonstrated that pancreatic cancer cells transfected with KRT17 siRNA showed lower Reactive-Oxygen-Species and mTOR/S6K1 phosphorylation levels, as well as reduced proliferation, migration and invasion [25].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“… 39 In addition, Chen et al discovered that inhibition of the proliferation of PANC‑1 human pancreatic cancer cells could be replicated by silencing of KRT17 through lentivirus‑mediated short hairpin RNA. 40 And it was found that upregulation of KRT17 promoted PDAC cell proliferation, invasion, and metastasis through EMT. 40 In addition, some studies raised concerns that overexpression of KRT17 mRNA was associated with a poor outcome for PDAC patients.…”
Section: Discussionmentioning
confidence: 99%
“… 40 And it was found that upregulation of KRT17 promoted PDAC cell proliferation, invasion, and metastasis through EMT. 40 In addition, some studies raised concerns that overexpression of KRT17 mRNA was associated with a poor outcome for PDAC patients. 41 In our study, RNA-seq analysis demonstrated that mRNA expression of KRT17 was markedly increased in cancer tissues compared to adjacent normal tissue.…”
Section: Discussionmentioning
confidence: 99%